2021
DOI: 10.3390/healthcare9101273
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Analysis of COVID-19 Vaccine Hesitancy among African Americans in the United States: A Recent Evidence

Abstract: African Americans have been disproportionately vaccinated at lower rates, which warrants the development of theory-based interventions to reduce vaccine hesitancy in this group. The fourth-generation theories, e.g., multi-theory model (MTM) of health behavior change, are vital in developing behavioral interventions. Therefore, the current study aims to determine recent trends in COVID-19 vaccination rates and to test the MTM model in predicting the initiation of COVID-19 vaccines among vaccine-hesitant Blacks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…In a study of university students' vaccine-accepting behaviors [27], only 50% reported that health care providers recommended COVID-19 vaccination. Young adults who hesitated to receive the vaccine were reported to have low beliefs about the benefits of the vaccine, indicating the need for a health promotion program [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of university students' vaccine-accepting behaviors [27], only 50% reported that health care providers recommended COVID-19 vaccination. Young adults who hesitated to receive the vaccine were reported to have low beliefs about the benefits of the vaccine, indicating the need for a health promotion program [28].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that vaccine hesitancy is not only a function of trust but also attributed to one's perception of low risk for the disease or carefree attitudes. This lends support to developing educational and m-health interventions based on fourth-generation behavioral theories [57]. These interventions may include simple yet interactive messaging, success stories, and testimonials from the community leaders [57].…”
Section: Vaccine Literacy and Vaccine Confidence Indexmentioning
confidence: 93%
“…This lends support to developing educational and m-health interventions based on fourth-generation behavioral theories [57]. These interventions may include simple yet interactive messaging, success stories, and testimonials from the community leaders [57]. To summarize, a successful vaccination campaign aiming to address and improve individuals' ability to appraise information and interventions to promote vaccine acceptance behavior will be critical.…”
Section: Vaccine Literacy and Vaccine Confidence Indexmentioning
confidence: 99%
“…The possible score range for MTM constructs was 0–12 units. The MTM tool is based on the fourth-generation behavioral theory and has a long-standing history to measure a variety of behaviors amidst the COVID-19 pandemic [ 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%